SENSORY PROFILE OF BRAZILIAN COFFEES BASED ON CONSUMER PERCEPTION AS AN ALTERNATIVE TO THE CONVENTIONAL METHODS - de Alcantara, Marcela; Freitas-Sá, Daniela De Grandi Castro (Coffee Science - ISSN 1984-3909, 2018)
Consumer-based methodologies for sensory characterization of foods have been widely discussed and are satisfactory, when compared to the results of trained panelists. However their efficiency in the description of complex foods rich in sensory attributes (flavor and aroma) such as coffee still needs to be explored. Polarized sensory positioning (PSP) is an innovative methodology for sensory characterization, based on the comparison of samples with reference products. In this study, roasted and ground coffees with different quality ratings according to the Coffee Quality Program (PQC) of the Brazilian Coffee Industry Association (ABIC) - Traditional, Superior and Gourmet – were evaluated by this method, applied to consumers. The beverage was presented to 100 consumers, who quantified the degree of global difference between the samples and the chosen references, using unstructured scales, followed by the verbal description of the sensory characteristics perceived in each sample evaluated. The samples were described for 30 attributes related to visual appearance, aroma, flavor, texture and hedonic terms. The method presented a good discriminative capacity, since it was able to differentiate the samples according to the PQC classification. In addition it allowed to identify the main sensory characteristics responsible for similarities and differences between the samples. The results indicate that consumers were able to infer about a quality classification based on their own perception and vocabulary, and the Brazilian traditional coffee was considered inferior to specialty coffees increasingly available in the market.